SYSTEMS AND PROCEDURES OF INTERN CONTROL ON PT. PANAMA AT SANGATTA - ., Robiansyah (EKONOMIA, 2013)
Research purpose is to determine payroll systems and procedures of intern control on PT. Panama at Sangatta. Research carried out for 3 months (April to Juni 2012) on PT. Panama at Sangatta, related to payroll systems and procedures. Research activifies includes : literature study, field observation, interviews, documentations, data collection and analysis. Collected data includes : general description of the company, organisational structure, payroll systems and procedures flow chart. Data analysis using comparrative analysis which compare between the systems applied by company and systems according to the theory.General analysis result is the payroll systems and procedures on        PT. Panama at Sangatta in fact already looking good. All the of supporting payroll documents are archived by numbers and stored property, but if compares to the theory there is still a shortage, so internal control elements can not be applied properly.